Temperature-induced changes in Arabidopsis Rubisco activity and isoform expression. (17th September 2022) - Cavanagh, Amanda P; Slattery, Rebecca; Kubien, David S
Abstract: In many plant species, expression of the nuclear encoded Rubisco small subunit (SSu) varies with environmental changes, but the functional role of any changes in expression remains unclear. In this study, we investigated the impact of differential expression of Rubisco SSu isoforms on carbon assimilation in Arabidopsis. Using plants grown at contrasting temperatures (10 °C and 30 °C), we confirm the previously reported temperature response of the four RbcS genes and extend this to protein expression, finding that warm-grown plants produce Rubisco containing ~65% SSu-B and cold-grown plants produce Rubisco with ~65% SSu-A as a proportion of the total pool of subunits. We find that these changes in isoform concentration are associated with kinetic changes to Rubisco in vitro : warm-grown plants produce a Rubisco having greater CO2 affinity (i.e. higher S C/O and lower K C ) but lower k catCO 2 at warm measurement temperatures. Although warm-grown plants produce 38% less Rubisco than cold-grown plants on a leaf area basis, warm-grown plants can maintain similar rates of photosynthesis to cold-grown plants at ambient CO2 and 30 °C, indicating that the carboxylation capacity of warm-grown Rubisco is enhanced at warmer measurement temperatures, and is able to compensate for the lower Rubisco content in warm-grown plants. This association between SSu isoform expression and maintenance of Rubisco activity at high temperature suggests that SSu isoform expression could impact the temperature response of C3 photosynthesis. Abstract : In Arabidopsis, growth temperature alters the expression of the Rubisco small subunit gene and protein family, which results in the expression of a Rubisco isoform with increased CO2 specificity at warm growth temperatures.